A systematic review of laparoscopic versus open abdominal incisional hernia repair, with meta-analysis of randomized controlled trials. (August 2015) - Al Chalabi, Hasanin; Larkin, John; Mehigan, Brian; McCormick, Paul
Abstract: Introduction: Development of an incisional hernia after abdominal surgery is a common complication following laparotomy. Following recent advancements in laparoscopic and open repair a literature review has demonstrated no difference in the short term outcomes between open and laparoscopic repair, concluding there was no favourable method of repair over the other and that both techniques are appropriate methods of surgical repair. However, long term outcomes in the available literature between these two approaches were not clearly analysed or described. The objective of this study is to assess the effectiveness and safety of laparoscopic versus open abdominal incisional hernia repair, and to evaluate the short and long term outcomes in regards to hernia recurrence using meta-analysis of all randomised controlled trials from 2008 to end of 2013. Study aims and objectives: Population : Patients who developed an abdominal hernia or abdominal incisional hernia following a laparotomy. Intervention : Two methods of surgical repair, laparoscopic and open abdominal wall hernia repair. Comparison : To compare between laparoscopic and open repair in abdominal wall incisional hernia. Outcome : length of hospital stay, operation time, wound infection and hernia recurrence rate. Methods : This study is a systematic review on all randomized controlled trials of laparoscopic versus open abdominal wall and incisional hernia repair. Medline, Pubmed, Cochrane library, Cinahl and Embase were the databases interrogated. Inclusion & exclusion criteria had been defined. The relevant studies identified from January 2008 to December 2013, are included in the analysis. The primary end point can be described as hernia recurrence, and secondary outcomes can be described as length of hospital stay post operatively, operation time and wound infection. Results: Five randomized controlled trials (RCTs) were identified and included in the final analysis with a total number of 611 patients randomized. Three hundreds and six patients were in the laparoscopic group and 305 patients in the open repair group. The range of follow up in the studies was two months to 35 months. The recurrence rate was similar (P = 0.30), wound infection was higher in the open repair group (P < 0.001), length of hospital stay was not statistically different (P = 0.92), and finally the operation time was longer in the laparoscopic group but did not reach statistical significance (P = 0.05) Conclusion: The short and long-term outcomes of laparoscopic and open abdominal wall hernia repairs are equivalent; both techniques are safe and credible and the outcomes are very comparable. Highlights: Safe and reliable method of hernia repair. The hospital stay between the two arms of the study is equal. The infection rate post operatively is higher in the open hernia repair group. The operation time is longer in the laparoscopic group but not statistically significant. The recurrence of hernia is the same between the study cohorts.